Rubén SÁNCHEZ MUÑOZ y Sandra GARCÍA PÉREZ (coord.), Meditaciones sobre la filosofía de Ortega, México, Universidad Veracruzana/Torres Asociados, 2016, 153 pp. - Sánchez Muñoz, Rubén; García Pérez, Sandra (Investigaciones Fenomenológicas, 2021)
-